Perceptions of selected female college students on the brand image of selected store window displays in Mtro Manila - Pablo, Ma. Teresa B. (College of Home Economics, University of the Philippines Diliman, 2011)
The study aimed to determine how selected female college students in Metro Manila perceived the brand images of store window displays of selected retail stores. Specifically, it aimed to (1) determine the images, lifestyle and overall impression young women have of the selected store window displays and if these were in line with the brands' projected image and objectives; (2) determine the various components of the selected store window display that affected the perceptions of the respondents; (3) determine how store windows affected consumer decisions to enter to buy from the store. Data was gathered with the use of a survey conducted among 40 selected female college students ages 18-22 years old chosen by purposive and convenience sampling and interviews with the various visual merchandisers of the selected stores. This data was interpreted using the point system method, weighted average, ranking, tabulation and summarization. The study concluded that colorful and attention grabbing window displays were viewed as the most attractive kind among the respondents. Th top three window display components that greatly affected the perceptions of the respondents were the following: styling of clothes, overall theme and the colors used. The images and lifestyle conveyed by the window displays as perceived by young women contributed to the overall impression they got. Generally, the store window displays of the four selected retail stores were able to project and effectively communicate the image and lifestyle their brands were all about except for Store C. Aside from reasons such as the attraction and relatability factor, various psychological motivations and consumer habits can also be the reasons behind certain decisions on entering and buying based on a store's window display.